2019
DOI: 10.1002/arch.21630
|View full text |Cite
|
Sign up to set email alerts
|

Changes in emergence phenology, fatty acid composition, and xenobiotic‐metabolizing enzyme expression is associated with increased insecticide resistance in the Colorado potato beetle

Abstract: The Colorado potato beetle (Leptinotarsa decemlineata) is a major agricultural pest of solanaceous crops. An effective management strategy employed by agricultural producers to control this pest species is the use of systemic insecticides. Recent emphasis has been placed on the use of neonicotinoid insecticides. Despite efforts to curb resistance development through integrated pest management approaches, resistance to neonicotinoids in L.decemlineata populations continues to increase. One contributing factor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…It is interesting to note that several genes coding for ATP-binding cassette transporters displayed increased transcript levels in imidacloprid-resistant L. decemlineata [ 45 ]. Furthermore, significant elevation of ATP-binding cassette subfamily G transporter transcript levels was observed in a commercially managed population of L. decemlineata that was imidacloprid-resistant when compared with an organically managed susceptible counterpart [ 46 ], which also supports the relevance of such transporters in insecticide resistance with respect to this insect pest. Functional annotation performed in the current work highlighted processes associated with multidrug resistance-associated protein 4, including response to oxidative stress.…”
Section: Discussionmentioning
confidence: 82%
“…It is interesting to note that several genes coding for ATP-binding cassette transporters displayed increased transcript levels in imidacloprid-resistant L. decemlineata [ 45 ]. Furthermore, significant elevation of ATP-binding cassette subfamily G transporter transcript levels was observed in a commercially managed population of L. decemlineata that was imidacloprid-resistant when compared with an organically managed susceptible counterpart [ 46 ], which also supports the relevance of such transporters in insecticide resistance with respect to this insect pest. Functional annotation performed in the current work highlighted processes associated with multidrug resistance-associated protein 4, including response to oxidative stress.…”
Section: Discussionmentioning
confidence: 82%
“…In a study of the internal extract of S. carnaria, Gołębiowski and co-workers found C20:5 to be present at 90-times higher concentrations in females than males; they propose that the compounds may play an important role in vitellogenesis 26 . Clements and co-workers 75 propose that arachidonic acid may play a role in the resistance of the Colorado potato beetle, Leptinotarsa decemlineata to neonicotinoid insecticide, and suggest that this may be associated with its regulatory role in cytochrome P450-dependent insecticide detoxification pathways. In the present study, a high concentration of C20:4 was observed in the extracts from the adults, which might suggest that S. argyrostoma is resistant to chemical insecticides; however, more detailed research is needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the proteome in resistant insects have also noted changes in physiology not directly related to detoxification. A correlation between fatty acid metabolism and insecticide resistance in CPB was observed when Δ9-desaturase, which is either synthesized de novo or directly obtained from diet, decreased as resistance to neonicotinoid increased [ 13 ]. Transcription analysis indicated that CYP6K1 and peroxidase were also correlated with insecticide resistance as the upregulated gene was associated with fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance can lead to different fitness costs in CPB [ 3 , 8 , 9 ], possibly due to the requirement for maintaining higher levels of metabolic or detoxification enzymes. There is evidence that insecticide resistance increases the energy needed to produce the metabolic enzymes required to detoxify the chemicals [ 10 , 11 , 12 ], altered fatty acid metabolism [ 13 ], and has been associated with behaviour changes [ 14 ]. CPB can also adapt to plant defenses, such as proteinase inhibitors, that negatively affect serine and cysteine digestive peptidases and reduce protein digestion [ 15 ] by changing the gut composition to avoid the plant’s defense mechanism [ 16 ].…”
Section: Introductionmentioning
confidence: 99%